Peningkatan Hasil Belajar Siswa dengan Model Problem Based Learning pada Pembelajaran Tematik Terpadu - Diana Puji Lestari; Nelly Astimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This type of research is classroom action research (PTK) using qualitative and quantitative approaches. Held in two cycles, the first cycle consisted of 2 meetings, and the second cycle consisted of 1 meeting. The subjects of the study were 26 fourth grade students of SDN 21 Taluak, Banuhampu Subdistrict. The results showed an increase. The study was conducted in two cycles. The results of the first cycle study on lesson plans averaged 81,25% (B), increasing in the second cycle to 96,8% (SB). The implementation of the first cycle on teacher activities averaged 87,5% (B), increasing in the second cycle to 96,4% (SB). The implementation of the first cycle on student activities averaged 87,5% (B), increasing in the second cycle to 96,42% (SB). Student learning outcomes in the first cycle averaged80,6% (B), increasing in the second cycle to 88,2% (SB) Thus, it can be concluded that the Problem Based Learning model can improve student learning outcomes in integrated thematic learning in elementary schools.